Cyclodextrin pendant polymer as an efficient drug carrier for scutellarin - Rongqiang Liao; Ying Liu; Pin Lv; Di Wu; Meiling Xu; Xiaoyuan Zheng (Taylor & Francis Group, 2020)
A novel β-cyclodextrin pendant polymer (ε-PL-CD), composed of poly(ε-lysine) (ε-PL) main chain and glycine-β-cyclodextrin (Gly-CD) side chains, was prepared by a simple two-step procedure. The ε-PL-CD was investigated as a drug carrier of hydrophobic drug scutellarin (SCU). The characterization and complexation mode of the SCU:ε-PL-CD were researched in both solution and solid state by means of photoluminescence spectroscopy, 1H and 2D NMR, X-Ray powder diffraction (XRPD), thermal gravimetric analysis, Particle size and Zeta potential. The solubility test indicated that the solubilizing ability of SCU:ε-PL-CD was significantly improved compared with SCU:β-CD and free SCU. Besides, in vitro cell experiment, it was found that SCU:ε-PL-CD has a strong inhibitory effect on the growth and invasion of tumor cells. The present study provides useful information for ε-PL-CD as a drug carrier material.